Budgetary analysis of the repair and comprehensive health care program 2006–2022 - Rivera Montero, Ricardo (Estado, Gobierno y Gestión Pública, 2021)
In this exploratory study on the Comprehensive Health Repair and Care Program (PRAIS), an analysis of the budget allocated in the period 2006- 2022 by the Budget Directorate for the program and the Undersecretary of Assistance Networks of the Ministry of Health (MINSAL) is developed, on which it depends. This to carry out a sectoral analysis of the budget.The importance of this analysis lies in the low amount of research related to PRAIS, even though this, from the international literature, has been cataloged as a successful case of reparation in the context of post-conflict societies. The findings made confirm the incrementalist nature of the public budget and a null critical analysis with a Human Rights perspective on the subject.